IMPACT OF QUALITY EDUCATION ON POVERTY REDUCTION ACROSS DIFFERENT ECONOMIC CONTEXTS - Sain, Zohaib Hassan; Amalia, Astrifidha Rahma; Furqan, Muhammad; A’yun, Rizqah Qurrata (JURNAL AL-IJTIMAIYYAH, 2024)
The impact of quality education on poverty reduction is a critical area of study, particularly when examined across different economic contexts. This research investigates how quality education influences poverty reduction in low-income and high-income countries, focusing on the moderating effect of financial context. A comparative cross-sectional research design was employed, utilizing secondary data from thirty countries—fifteen low-income and fifteen high-income—sourced from reputable databases such as the World Bank, United Nations Educational, Scientific and Cultural Organization (UNESCO), and Organisation for Economic Co-operation and Development (OECD). Descriptive statistics, correlation analysis, and multiple regression were conducted to analyze the relationship between educational quality and poverty reduction. The findings reveal a significant positive correlation between literacy rates and poverty reduction, mainly in high-income countries (r = 0.76, p < 0.01). Regression analysis further supports that the impact of education on poverty is more substantial in high-income contexts, with a notable interaction effect between education and economic context (β = 0.36, p < 0.01). These results suggest that while education is vital for poverty alleviation, its effectiveness varies depending on the economic environment. The study concludes that tailored educational policies are necessary to enhance the poverty-reducing potential of education in low-income countries, highlighting the need for global educational reforms to address these disparities.